3D-Simulation of low-grade coal combustion in the combustion chamber - Askarova, A.S.; Bolegenova, S.A.; Maksimov, V.Yu.; Maksutkhanova, A.M.; Shortanbayeva, Zh.K.; Ospanova, Sh.S. (Recent Contributions to Physics, 2013)
This paper describes the application of 3-D modeling to the study of heat and mass transfer processes occurring during combustion of energy fuels in existing power plants combustion chambers. Studies have been conducted on the basis of 3-dimensional Navier-Stokes equations, the energy and mass transfer with the heat, radiant heat, chemical reactions and multiphase environment.There had been built the geometry of the combustion chamber with all the technical characteristics of the BKZ-75 Shakhtinskaya CHP. The algorithm of the task, a numerical method for research was taken. Main characteristics of the turbulent heat transfer process in high-temperature environments in the presence of physical and chemical transformations was obtained.